Copyright Infringement in Online Media: Corporate Legal Liability - Maha Wiryanthi, Ni Putu Ega (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
This study examines the legal responsibilities of online media companies in addressing copyright violations, focusing on regulatory frameworks, technological implementations, and enforcement challenges. Using a normative juridical approach, this research analyzes Indonesia’s Copyright Law No. 28 of 2014, the DMCA, and the EU Copyright Directive. It also includes comparative case studies such as Viacom vs. YouTube (2007), Google Books Litigation (2015), and TikTok Copyright Infringement (2021) to assess evolving legal frameworks and platform liability in managing user-generated content (UGC).Findings reveal that while platforms employ AI-powered Content ID, automated filtering, and blockchain copyright management, these technologies face false positives, jurisdictional enforcement difficulties, and takedown notice transparency issues. The cross-border nature of the internet complicates legal enforcement, necessitating global cooperation and harmonized copyright policies. A multifaceted approach is needed, integrating technological innovation, stronger regulations, and stakeholder collaboration. Enhancing cross-border legal cooperation and content moderation policies is vital to balancing copyright enforcement with freedom of expression. Collaboration among digital platforms, governments, and industry stakeholders is key to ensuring a sustainable and legally balanced digital ecosystem for copyright protection and creative industry growth